Benefits and challenges of collaborative networks addressing food system disruptions during the COVID-19 pandemic - Dahal, Dikshya; Schusler, Tania M. (Frontiers in Sustainable Food Systems, 2025)
The COVID-19 pandemic disrupted food systems with disproportionate impacts on marginalized social groups, which in the USA included racial and ethnic minorities, working class families, immigrants, seniors, and people with disabilities, among others. The pandemic also greatly affected the operations of nonprofit organizations, which play important roles in disaster response. We explored how social networks supported non-profit organizations’ efforts to address increased food insecurity and food-related business disruptions during the pandemic in the Chicago region, IL, USA. We used mixed methods including a Social Network Analysis (SNA) of 48 organizations and their reported partners plus focus group discussions with representatives of 20 organizations to learn about their experiences. SNA revealed that partnership interactions occurred more often among organizations of similar type or within the same sector, although cross-sectoral interactions also took place. Over half of the interactions occurred through established relationships among organizations, while at least 32% of interactions involved newly created partnerships. Focus group participants reported that partnering with other entities was essential to implement program activities, increase resources (e.g., funding, volunteers, food and supplies for distribution, facilities or land), and expand outreach and services to broader audiences. Yet, participants also described challenges of collaboration, such as disrespectful treatment, inequitable workloads, and poor coordination among some partners. Building genuine relationships, clarifying roles, sharing resources equitably, and fostering trust through transparency and accountability were recommended for effective partnerships. Our results demonstrate the importance of social networks to overcome challenges caused by disasters and suggest directions for future research exploring how to foster cross-sectoral collaborations to create equitable, sustainable, and resilient food systems.